G499(P) Child safety awareness in medical students: a need for the lollipop lady. (27th April 2015) - Bali, S; Jacob, H; Fertleman, C
Abstract : Aims: Advocating to improve child safety, as part of child health promotion, is integral to the role of all doctors working with children. Many general practitioners and doctors in training shy away from providing such advice to families because they lack the knowledge, missing important opportunities to prevent accidents in children. Variation in postgraduate rotations make medical school an ideal time to learn about child safety, a practice followed in the United States of America. Our study explored medical students knowledge, skills and attitudes towards providing guidance about child safety. Methods: We sent a survey to all medical students undertaking their paediatric placement at one teaching hospital between 2012–13. We asked them if they felt comfortable giving advice about preventing sudden unexpected infant death, drowning and choking as well as cardiopulmonary resuscitation (CPR) and first aid. We also enquired from them about the commonest causes of death in children under five and the risk factors for accidental deaths in children. We collected the data using SurveyMonkey™ software and analysed it using Microsoft Excel™. Results: 82 students were approached, 49(60%) responded. Most [32(65%)] felt uncomfortable giving parents advice about preventing sudden unexpected death in an infant, many [22(47%)] about drowning advice and some [19(39%)] about preventing choking. 15(30%) felt uncomfortable giving parents advice about CPR and first aid. 27(55%) thought that accidents were a leading cause of death in children under five. 49(100%) learnt about child safety from personal experience while 26(53%) learn about it from general practice or child health placements. 43(88%) of respondents wanted these topics to be covered during medical school. A recent survey of 56 UK paediatricians and general practitioners rated highly the importance of undergraduate knowledge of accident prevention 3.7/5 and ability to engage in health promotion 4/5. Conclusions: This study demonstrates a lack of confidence and competence among medical students to provide advice about child safety despite clinicians considering this topic essential to undergraduate knowledge. Efforts must be made to improve the quality of child safety and child health promotion advice given to parents and undergraduate training provides an ideal opportunity to develop these skills.